2007
DOI: 10.1037/0735-7036.121.4.372
|View full text |Cite
|
Sign up to set email alerts
|

Serial reversal learning and the evolution of behavioral flexibility in three species of North American corvids (Gymnorhinus cyanocephalus, Nucifraga columbiana, Aphelocoma californica).

Abstract: In serial reversal learning, subjects learn to respond differentially to 2 stimuli. When the task is fully acquired, reward contingencies are reversed, requiring the subject to relearn the altered associations. This alternation of acquisition and reversal can be repeated many times, and the ability of a species to adapt to this regimen has been considered as an indication of behavioral flexibility. Serial reversal learning of 2-choice discriminations was contrasted in 3 related species of North American corvid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
242
1
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 224 publications
(254 citation statements)
references
References 69 publications
(79 reference statements)
10
242
1
1
Order By: Relevance
“…a single presentation), they needed at least three times fewer presentations to successfully complete the associative learning tasks than what is commonly used in studies testing similar abilities in bird species (e.g. [9,10,14,15] and references therein). This result was unexpected and suggests a possible difference in the tempo at which associations are formed between these groups; further studies are needed to explore the generality of these results.…”
Section: Discussionmentioning
confidence: 99%
“…a single presentation), they needed at least three times fewer presentations to successfully complete the associative learning tasks than what is commonly used in studies testing similar abilities in bird species (e.g. [9,10,14,15] and references therein). This result was unexpected and suggests a possible difference in the tempo at which associations are formed between these groups; further studies are needed to explore the generality of these results.…”
Section: Discussionmentioning
confidence: 99%
“…One possibility is that these sex differences are related to the different social and parental roles of males and females. For example, some authors [1,13] have suggested that the evolution of flexible behaviours may be promoted by high parental investment and complex social life, two traits that differ markedly between male and female guppies [21,22].…”
Section: Discussionmentioning
confidence: 99%
“…Yet sometimes the environment changes rapidly, and individuals must be able to inhibit a previously learned behaviour to issue a new, more appropriate response. The degree of cognitive flexibility varies considerably among species [1], but substantial individual variation for this trait is also reported within species, for example in relation to age or personality [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…The best established extension is expressed in the verdict of homology between the mammalian and avian hippocampus, which reflects a recent sea change in thinking about the neural substrates of cognitive flexibility in birds (Columbo & Broadbent, 2000). Further bolstering this extension, a body of excellent, interdisciplinary comparative work has been conducted by Kamil, Balda, Bond, and associates investigating correlations between multiple forms of behavioral flexibility and hippocampal volume in corvids (Kamil, Balda, & Olsen, 1994;Bond, Balda, and Kamil, 2007). A recognizable form of the hippocampal formation dates back to fish, and Day presents a cladogram summarizing evidence that the formation supports a cluster of cognitive capacities across a swathe of vertebrates (Day, 2003).…”
Section: Proposal 1: the Mtlsmentioning
confidence: 99%